PENGARUH LATIHAN SHOULDER PRESS DAN TRICEPS EXTENSION TERHADAP KEKUATAN OTOT LENGAN DAN HASIL RENANG GAYA BEBAS 100 METER PUTRA KU II BEAVER SWIMMING CLUB TAHUN 2026 - Torang Mangapul Pandapotan Situmorang; Amansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of shoulder press and triceps extension training on arm muscle strength and 100-meter freestyle swimming performance of male KU II athletes at Beaver Swimming Club in 2026. This study employed an experimental method using a one group pretest–posttest design. The sample consisted of six male athletes selected through purposive sampling. The training program was conducted for 16 sessions. Arm muscle strength was measured using an expanding dynamometer, while swimming performance was assessed through a 100-meter freestyle swimming test. Data were analyzed using descriptive statistics, the Liliefors normality test, and the paired sample t-test at a significance level of 0.05. The results showed that the training program significantly improved arm muscle strength and swimming performance. The paired sample t-test indicated that the calculated t value for arm muscle strength (3.162) and swimming performance (5.34) exceeded the critical t value (2.571), indicating significant improvements after the intervention. It can be concluded that shoulder press and triceps extension training effectively increase arm muscle strength and improve 100-meter freestyle swimming performance. Therefore, these exercises are recommended as part of the physical conditioning program for competitive swimmers.